Numerical analysis of the influence of liquid on propagation of a rolling contact fatigue crack - M. Olzak; J. Piechna Warsaw; P. Pyrzanowski (Fracture and Structural Integrity)
Numerical investigations of the propagation of rolling contact fatigue crack filled by the liquid have been conducted. Two models of fluid crack interaction have been considered. In the first model called 䖓hydrostatic the assumption of incompressible, inviscid and weightless liquid was accepted. It was also assumed that due to the wheel load the trapped liquid could not get outside the crack and its volume remained constant until the rising pressure would open up the crack mouth again. On this assumption the analysis has a steady-state character. In the second model it has been assumed that the crack is filled by the viscous, incompressible fluid and the fluid motion as well as the resulting pressure distribution can be represented by one-dimensional form of the Reynolds equation. The method for solving the problem of the coupled motion of liquid and crack faces has been developed and series of calculation were made. The method has been employed for the predicting of crack deformation in the course of wheel rolling